Carbonização hidrotérmica de lodo de esgoto: caracterização do hidrocarvão e análise estatística de nutrientes e poluentes na fase líquida - Canencio, Kevin Nabor Paredes (2025)
Hydrothermal carbonization (HTC) of sewage sludge has significant potential for providing bioenergy and nutrients and can contribute to conventional wastewater treatment. However, more research needs to focus on sewage sludge from primary clarifiers with high moisture content in order to optimize the treatment process and maximize its volume reduction efficiency. This study examines the physical and chemical properties of HTC from primary sludge obtained from a sewage treatment plant, analyzing conditions such as temperature (180-220°C), reaction time (60-120 minutes) and pH (6.5- 12). The Principal Component Analysis (PCA), Sensitivity Analysis and Response Surface Analysis (RSM) techniques were used to study the liquid phase; Techniques such as scanning electron microscopy (SEM), X-ray diffractometry (XRD), X-ray fluorescence (XRF) and Fourier transform infrared vibrational spectroscopy (FTIR) were applied to the solid phase. The results show that temperature markedly affects the hydrochar yield, higher calorific value (HHV) and macronutrients, such as total Kjeldhal nitrogen, ammoniacal nitrogen, potassium, almost all micronutrients evaluated, with a greater influence (88%) on iron concentrations. Time had a moderate influence in relation to organic nitrogen, and micronutrients such as Si, Ca, Se and Mn. The pH significantly influenced the concentrations of macro and micronutrients (P, S, Al, Mg, Ni, Mo) as well as the concentrations of pollutants especially As and Ba. Despite the potential of hydrochar as a biofuel, simple optimization of variables is insufficient to obtain high HHV, indicating the need for co-HTC approaches. The liquid phase has great potential as a biofertilizer due to the high levels of nutrients and the low content of heavy metals, although the high chemical oxygen demand may limit its use. Future research should explore the application of the liquid phase of HTC primary sewage sludge in agricultural activities.